Interculturality in Health: The pending issue of the Mexican Health System - Ávila Domínguez, Rosangela (Mexican Journal of Medical Research ICSA, 2018)
Interculturality is a process of communication and interaction between people of different cultures in which the integration and harmonious coexistence between them is favored. Mexican population has a strong feeling for the ethnic belonging; regardless if they speak an indigenous language or not. However, there is a significant gap in health conditions of indigenous groups due to geographical dispersion and isolation, in addition to the discriminatory treatment they receive, which is because their needs and demands are not met. The present review is focused on critically analyze the current situation of interculturality in health, pointing out inclusion strategies adopted by other countries and emphasizing that this is a pending issue for the Mexican Health System, which leads to the conclusion that interculturality has a great importance in public policies and work strategies focused on the well-being of indigenous peoples.